2015
DOI: 10.3892/or.2015.4039
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-429 inhibits the migration and invasion of colon cancer cells by targeting PAK6/cofilin signaling

Abstract: MicroRNAs (miRs), a class of non-coding RNAs 18-25 nucleotides in length, can lead to mRNA degradation or inhibit protein translation by directly binding to the 3'-untranslational region (UTR) of their target mRNAs. The deregulation of miR-429 has been suggested to be involved in the development and progression of colon cancer. However, the detailed molecular mechanism involved remains to be determined. The aim of the present study was to investigate the role of miR-429 in the regulation of migration and invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…The in vitro studies and the summary of their results are described in Table 1. 12 20,21 This reduced cellular invasion and migration. Epigenetic regulation is a crucial part of determining the expression of miR-200 family.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The in vitro studies and the summary of their results are described in Table 1. 12 20,21 This reduced cellular invasion and migration. Epigenetic regulation is a crucial part of determining the expression of miR-200 family.…”
Section: Resultsmentioning
confidence: 96%
“…A number of groups have identified that treatment with a demethylating agent causes subsequent upregulation of miR-200b and miR-429 in hypermethylated cell lines. 20,21 This reduced cellular invasion and migration. 21 Fessler et al demonstrated epigenetic methylation of the miR-200 family promoter regions is associated with miR-200 family repression and a mesenchymal phenotype in a group of clinical samples.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…PAK6 may also be involved in stress-signaling as it is stimulated by p38-MAP kinase (Kaur et al, 2005). Expression of PAK6 is targeted by miR-328 and miR-23a in prostate cancer cells (Liu et al, 2015; Cai et al, 2015), and by miR-429 in colon cancer cells (Tian et al, 2015). PAK6 interacts with the cell junction protein IQGAP1 in a kinase activity-dependent manner and regulates the dissociation of cell-cell junctions in growth factor-stimulated cells (Fram et al, 2014; Morse et al, 2016).…”
Section: Pak6 Biologymentioning
confidence: 99%